Cien años de la edición del Curso de Lingüística General: la herencia saussureana - Filinich, María Isabel (2018)
The centennial anniversary of the Course in General Linguistics represents an opportunity to look through a work that allow us to access —albeit indirectly and in no few aspects simplified— to a way of thinking that would revolutionize not only linguistics but epistemology as a whole. This analysis benefits from the edition of manuscripts originally published in 2002, and translated into Spanish in 2004, under the title Escritos sobre Lingüística General, in the light of which the content of the Course is both deepened and widened. It is from this point of view that we evoke those Saussure’s reflections that led to a transformation of the episteme in the field of humanistic and social disciplines.